Reticular pseudodrusen: A critical phenotype in age-related macular degeneration. (May 2022) - Wu, Zhichao; Fletcher, Erica L.; Kumar, Himeesh; Greferath, Ursula; Guymer, Robyn H.
Abstract: Reticular pseudodrusen (RPD), or subretinal drusenoid deposits (SDD), refer to distinct lesions that occur in the subretinal space. Over the past three decades, their presence in association with age-related macular degeneration (AMD) has become increasingly recognized, especially as RPD have become more easily distinguished with newer clinical imaging modalities. There is also an increasing appreciation that RPD appear to be a critical AMD phenotype, where understanding their pathogenesis will provide further insights into the processes driving vision loss in AMD. However, key barriers to understanding the current evidence related to the independent impact of RPD include the heterogeneity in defining their presence, and failure to account for the confounding impact of the concurrent presence and severity of AMD pathology. This review thus critically discusses the current evidence on the prevalence and clinical significance of RPD and proposes a clinical imaging definition of RPD that will help move the field forward in gathering further key knowledge about this critical phenotype. It also proposes a putative mechanism for RPD formation and how they may drive progression to vision loss in AMD, through examining current evidence and presenting novel findings from preclinical and clinical studies.